Evidence for various interventions to reduce depressive symptoms for children and adolescents: protocol of a global evidence and gap map - Pengpeng Cao; Yuhao Li; Luyao Yang; Liping Guo; Jiyixi Hua; Shuo Zhang; Chuying Li; Bingxia Dang; Yanzhuang Sun; Ming Liu; Zheng Xu; Kehu Yang; et al. (Systematic Reviews)
Abstract Background Children and adolescent depression conditions are responsible for high levels of disability burden and negatively influence academic participation and life-long outcomes while their interventions and outcomes remain controversial. Methods We conducted a comprehensive search in multiple databases of primary studies. The EPPI‐Mapper mapping tool was applied to present identified studies as framework-described results. Discussion This is the protocol for an evidence and gap map (EGM). The objectives of this EGM are to identify and map all randomized controlled studies (RCTs) on universal, school-based social and emotional learning programs for children and adolescents with depressive symptoms or diagnoses of depression, and to identify existing gaps in the evidence for creating an interactive, searchable, and publicly accessible EGM. The map will provide insights for researchers and decision-makers, build on the evidence bases in this field, and identify key areas for future research. Systematic review registration Campbell Systematic Reviews cl2.20240091.